School-Age Outcome of Fetuses with Isolated Complete Septum Pellucidum Agenesis at Prenatal Magnetic Resonance Imaging - Righini, Andrea; Izzo, Giana; Doneda, Chiara; Scelsa, Barbara; Parazzini, Cecilia (Neuropediatrics, 2021)
Objective To the best of our knowledge, there have not been studies to address the issue of long-term follow-up of patients with prenatal diagnosis of isolated complete septum pellucidum agenesis (SPA). The aim of this study was to acquire information about the school-age outcome of such patients as a resource for counseling parents receiving this prenatal finding.Methods From a large fetal magnetic resonance (MR) database, we selected only those cases with isolated complete SPA as confirmed by two senior pediatric neuroradiologists in consensus; we then gathered information from the parents of those children who had reached the school age.Results None among the 12 cases (mean age at follow-up: 8.7 years, range: 6–13 year) of the resulting final cohort presented visual or stature deficits; only one required special teaching assistance in school. All other 11 children resulted without any notable academic issue.Conclusion Our report may provide information of practical value about the school-age outcome of fetuses detected by prenatal MR imaging to carry isolated complete SPA.
Keywords: fetal MR imaging; prenatal diagnosis; septum pellucidum; fetal brain